Unravelling the role of Sildenafil and SB204741 in suppressing fibrotic potential of peritoneal fibroblasts obtained from PD patients - Chaturvedi, Saurabh; Singh, Harshit; Agarwal, Vikas; Jaiswal, Akhilesh; Prasad, Narayan (Frontiers in Pharmacology, 2024)
Peritoneal fibrosis (PF) results in technique failure in peritoneal dialysis (PD) patients.Peritoneal fibroblasts are characterized by increased ACTA2 gene, responsible for alpha smooth muscle actin (−S) extracellular matrix (ECM) production and inflammatory cytokines production are key mediators in the pathogenesis of PF. 5-hydroxytryptamine (5-HT; serotonin) induces ECM synthesis in fibroblasts in a transforming growth factor-beta 1 (TGF-β1) dependent manner. The purpose of our study was to identify the potential mechanism and role of Sildenafil and 5HT2B receptor inhibitor (SB204741) combination in attenuating PDassociated peritoneal fibrosis. Studies were performed to determine effect of TGF-β1, Sildenafil and SB204741 on human peritoneal fibroblasts (HPFBs) isolated from parietal peritoneum of patients on long term PD patients (n=6) and controls (n=6). HPFBs were incubated with TGF-β1 (10ng/ml) for 1 hour and later with TGF-β1 (10ng/ml)/ [Sildenafil (10µM) or SB204741 (1µM)] and their combination for 24 hours (post-treatment strategy). In the pre-treatment strategy, HPFBs were pre-treated with [Sildenafil (10µM) or SB204741 (1µM) and a combination of the two for 1 hour and later with only TGF-β1 (10ng/ml) for 24 hours. The anti-fibrotic effects of combination Sildenafil and SB204741 was greater than each drug alone. In TGF-β1 stimulated HPFBs, pro-fibrotic genes (COL1A1, COL1A2, ACTA2, CTGF, FN1, TGFΒ1, TGFB1) exhibited higher expression compared to controls which are crucial targets of Sildenafil and SB204741 against peritoneal fibrosis. Synergistic approach played an anti-fibrotic role through regulating the pro and anti-fibrotic gene responses as well as inflammatory cytokine responses. Combination treatment significantly attenuated peritoneal fibrosis, as evident by almost complete amelioration of ACTA2 expression, restoration of antifibrotic genes (MMP2/TIMP1), and at least, by reducing the expression of pro-inflammatory cytokines (IFN- IL-4, IL-17, IL-1β, IL-6, TNF- TGF-β1) along with increase in IL-10 levels. Taken together, the above research evidence, combination of Sildenafil and SB204741 may have therapeutic potential in suppressing peritoneal fibrosis due to peritoneal dialysis.